The application of respiratory muscle training to competitive rowing - Griffiths, L. A. (2010)
Respiratory muscle training (RMT) has been shown to improve exercise tolerance during a wide range of exercise modalities and durations of activity (McConnell & Romer, 2004b). However, there is a limited amount of research characterising the influence of RMT in specific athletic populations, or examining any sport-specific factors that may influence the benefits of RMT. Hence, the purpose of this dissertation was to evaluate the application of RMT in competitive rowers and to explore methods of optimising this to rowing. Results: Inspiratory muscle training (IMT) increased inspiratory muscle strength (~20-29%; p < 0.05) and attenuated inspiratory muscle fatigue (~8-28%; p < 0.05) during time trial performance in club-level and elite rowers. However, only in the club-level oarsmen was IMT associated with a measurable improvement in rowing performance (2.7% increase in mean power; p < 0.05). Expiratory muscle training (EMT) provided no ergogenic effect, and concurrent EMT and IMT did not enhance performance above that seen with IMT alone. IMT loads performed at 60-70% of maximal inspiratory mouth pressure (PImax) were equivalent to the widely used 30 repetition maximum, which is higher than reported for non-rowers (Caine & McConnell, 1998a); further, a load of 60% PImax was sufficient to activate the inspiratory muscle metaboreflex, as evidenced by a time-dependent rise in heart rate (70.1 ± 13.2 to 98.0 ± 22.8 bpm; p < 0.05) and mean arterial blood pressure (92.4 ± 8.5 to 99.7 ± 10.1 mmHg; p < 0.05). Higher and lower inspiratory loads did not activate the metaboreflex. Assessments of flow, pressure and volume in rowing relevant postures revealed no significant impairments, but optimal function occurred in the most upright postures. Conclusions: These data support the application of IMT, but not EMT, in elite and sub-elite rowers, and suggest that a load of 60-70% of PImax provides metaboreflex activation during loading. Further, the data do not support a requirement to undertake IMT in rowing relevant postures.